The role of Strategic Planning in Crisis Educational Management at Tishreen University from Their worker Perspectives - Mohamed, Mahmoud; محمود, نورا (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aimed to identifying the Opinion of Sample of worker at Tishreen University in the role strategic Planning importance, Crisis Educational Management, also to define the differences in Opinion of Sample to these variable the scientific qualification. To achieve the objectives of this research, questionnaire has included the role of Strategic Planning in Crisis Educational Management consisted of (52) items, has been applied during the academic year of (2015 - 2016) on sample (278) members, The present research used the descriptive analytical approach. Validity of the questionnaire was established though a jury of (7) of the teaching staff of educational at Damascus and Tishreen. The final results showed that the role of Strategic Planning in Crisis Educational Management were middle degree. In fact there are no found differences between the sample answers, about the strategic Planning importance, and their role in Crisis Educational Management according to variable the scientific qualification. The Research presented suggestions concerning of to adopt strategic planning as a tool for changing and developing administrative work and specialized workshops in strategic Planning.